Efficient Data Collection Using Randomized Multipath Routes in WSN - Basu, M. Trinath; Venkatesh, G; Srikanth, Immidi (International Journal of Computer Sciences and Engineering, 2014)
Wireless Sensor Networks (WSNs) are vulnerable to attacks such as Denial of Service (DoS) and compromised-node. This is due to the nature of the existing multi-path routing mechanisms which are deterministic in nature. Adversaries can steal information by compromising routing algorithm in WSN. In this paper we propose routing mechanisms where randomized multi-path routes are dynamically computed. Such routes can bypass the black holes made though DoS and compromised node attacks .The generated routes are energy efficient besides dispersive in nature. Simulation results reveal that the proposed mechanisms are energy efficient in bypassing black holes.